Antibodies against SARS-CoV-2 in unvaccinated children hospitalized with COVID-19: An observational cohort study of pre-Omicron and Omicron variants era. - Rattapon Uppala; Phanthila Sitthikarnkha; Kiatichai Faksri; Pope Kosalaraksa; Leelawadee Techasatian; Nattakarn Tantawarak; Sysavanh Nanthavongsa (PLoS ONE)
Purpose This study aimed to investigate the antibodies against SARS-CoV-2 in children hospitalized due to COVID-19 during the era of pre-Omicron and Omicron variants. Methods This was a retrospective observational study conducted at a tertiary academic medical center in Thailand between June 2021 and August 2022. We collected the data of children aged under 18-year who were hospitalized from SARS-CoV-2 infection. After hospital discharge, we scheduled clinical follow-up 60 to 90 days post-infection clinical follow-up. We measured antibodies against SARS-CoV-2 anti-spike protein receptor-binding domain in the serum during a follow-up visit and compared the mean difference of antibody levels between children infected with COVID-19 during the pre-Omicron and Omicron eras. Results A total of 119 children enrolled into the study. There were 58 and 61 children hospitalized due to COVID-19 during pre-Omicron and Omicron era, respectively. The median (interquartile range, IQR) of SARS-CoV-2 antibodies in all cases was 206.1 (87.9-424.1) U/mL at follow-up. Children infected during pre-Omicron had SARS-CoV-2 antibody levels at follow-up higher than children infected during Omicron era [mean difference 292.57 U/mL, 95% CI 53.85-531.28, p = 0.017). There was no difference in SARS-CoV-2 antibody levels between the children based on gender, age, co-morbidities, chest radiograph classification, or diagnosis. Conclusions The antibodies response to SARS-CoV-2 infection was weaker during the Omicron era than previous variant of concern. Immunization strategies and policies should be implemented in children even if they had been previously infected.